The formation mechanism of landslides in typical fault zones and protective countermeasures: A case study of the Nanpeng River fault zone - Li, Youjun; Zhang, Hongri; Huang, Liming; Li, Hongming; Wu, Xuexiao (Frontiers in Earth Science, 2023)
Landslides are frequent in the Nanpeng River fault zone in southwest Yunnan. Based on the Zhenqing Expressway survey, we studied the geological conditions and landslide characteristics of landslides in the above area. The researcher found the geological background of the area as the cause of the local high steep slopes and broken rock masses. Fault-type and accumulation landslides mainly occur in this area. The formation of fault-type landslides is related to endogenous causes such as tectonic movements, but they are less easily triggered than mounded landslides. Accumulation landslides are related to broken rock masses and are sensitive to external factors, such as rainfall and artificial unloading. The coordinated control of permanent support engineering measures, local deformation control measures, and overall support reinforcement should be considered as preventive measures.